Psychological Empowerment and Employee Turnover Intention: The Moderating Role of Organisational Diversity Climate - Ojih, Emmanuel Eche; Ejikeme, Gray Goziem; Orshi, Julie Onyowoicho Enewa (NIU Journal of Social Sciences; Vol 9 No 2 (2023): NIU Journal of Social Sciences, Vol. 9 No. 2, June 2023, 2023)
The study explored the relationship between psychological empowerment and employee turnover intention while examining the moderating effects of perceived organizational diversity climate and workplace prejudice. The study adopted the correlational design in line with the positivist research philosophy. The study participants comprised employees of service and manufacturing organizations in the public and private sectors. They comprised four hundred and thirty-one (N = 431) with a mean age of 35.8 years (SD = 9), comprising 234 male and 197 female employees randomly selected from six organizations. The Work Diversity Inventory (WDI), the Workplace Prejudice/Discrimination Inventory (WPDI), the Measuring Empowerment Questionnaire (MEQ), and the Turnover Intention Scale (TIS-6) were used as measures of the study variables. Four hundred and thirty-one (431) questionnaires were returned valid. Simple linear regression and Multiple Linear Regression (MLR) were used to test the study hypotheses. The results revealed that psychological empowerment has a significant positive relationship with employee turnover intention (β = .028, t = 2.070, p = .039). There was a significant moderation effect of perceived organizational diversity climate on the relationship between psychological empowerment and employee turnover intention (β = - .002, t = - 2.812, p = .005), accounting for a 1.8% variance in employee turnover intention. The study concluded that organizational diversity climate reduces the positive correlation between empowerment and intention to leave. The study recommended strengthening empowerment practices, fostering a positive diversity climate, and routine evaluation of climate diversity among employees.